2015
DOI: 10.1371/journal.pone.0119154
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Novel Gammapapillomaviruses, HPV179 and HPV184, Isolated from Common Warts of a Renal-Transplant Recipient

Abstract: Gammapapillomavirus (Gamma-PV) is a diverse and rapidly expanding PV-genus, currently consisting of 76 fully characterized human papillomavirus (HPV) types. In this study, DNA genomes of two novel HPV types, HPV179 and HPV184, obtained from two distinct facial verrucae vulgares specimens of a 64 year-old renal-transplant recipient, were fully cloned, sequenced and characterized. HPV179 and HPV184 genomes comprise 7,228-bp and 7,324-bp, respectively, and contain four early (E1, E2, E6 and E7) and two late genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…Our observations are not surprising since previous studies have demonstrated that typically cutaneous HPV types (Beta-and Gamma-PVs) were relatively common in the mucosal epithelia, suggesting a possible dual tissue tropism of the majority of HPV species [1,13,32,28,45,46]. In addition, two Gamma-PV types were identified in a surface swab of a genital wart and a cervical cancer biopsy sample, possible as part of the normal mucosal microbiota, as reported previously [23,26].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our observations are not surprising since previous studies have demonstrated that typically cutaneous HPV types (Beta-and Gamma-PVs) were relatively common in the mucosal epithelia, suggesting a possible dual tissue tropism of the majority of HPV species [1,13,32,28,45,46]. In addition, two Gamma-PV types were identified in a surface swab of a genital wart and a cervical cancer biopsy sample, possible as part of the normal mucosal microbiota, as reported previously [23,26].…”
Section: Discussionsupporting
confidence: 87%
“…Samples of total DNA (n = 458), extracted from 249 swabs of the anal canal (226 initial and 23 follow-up samples), 94 cervical cancer formalin-fixed paraffinembedded (FFPE) tissue samples, 21 genital warts (11 swabs and 10 biopsies) from different anatomical sites [foreskin (n = 4), scrotum (n = 2), penile glans (n = 2), perianal area (n = 4) and pubis (n = 9)], and 94 oral swabs collected during routine paternity testing, were obtained from the archival collection of samples of the Instituto de Biología Molecular y Celular de Rosario (Rosario, Argentina) and the Institute of Microbiology and Immunology, Faculty of Medicine, University of Ljubljana (Ljubljana, Slovenia). Before subsequent analyses, all samples were collected, processed, and stored at − 80°C, as described previously [11,27,[29][30][31][32]. The adequacy of samples for downstream analyses was determined by PCR amplification of the human beta-globin gene, as previously described [33].…”
Section: Patients' Data Sample Collection and Processingmentioning
confidence: 99%
“…In 11/18 (61.1%) cutaneous warts with low viral load of Mu -PVs, we concomitantly detected cutaneous wart–associated Alpha -PVs (HPV2, HPV27, and HPV57), which were the most probable etiological agents of these warts [52, 54]. As shown in Table 3, we did not detect any additional cutaneous wart-associated HPV types in seven cutaneous warts, suggesting the involvement of rarer cutaneous wart-associated HPV types, such as HPV125, HPV179, and HPV184 [24, 44] or potentially novel HPV types. Second, the low viral load of Mu -PVs in these lesions could be a result of the dilution of Mu -PV–infected cells with heterogeneous, non-targeted cell populations.…”
Section: Resultsmentioning
confidence: 95%
“…Namely, in sporadic cases of common warts concurrent infections with two or more HPV types can be identified, including their well-known etiological agents, such as HPV1, HPV2, HPV4, HPV7, HPV27, HPV57, and HPV65 (3,7,10,26,32). Because one of the surrogate markers for determining the etiology of common warts is the estimation of the viral load of each HPV type present in the lesion of question (7,35,52), HPV2/27/57 multiplex RT-PCR can be used in combination with other quantitative HPV type-specific RT-PCRs to identify the HPV type with the highest HPV viral load and consequently the highest probability of being a "true" etiological agent of the investigated common wart.…”
Section: Discussionmentioning
confidence: 99%
“…genome sequences of targeted HPV types retrieved from the GenBank database (accession nos. X55964, EF117890, EF117891, EF362754, EF362755, X74473, AB211993, X55965, U37537, and AB361563) were aligned using the MAFFT v6.846 algorithm (34), as described previously (35). After evaluating the multiple alignment of complete HPV2, HPV27, and HPV57 genome sequences, the HPV L2 gene was selected as the most appropriate target region.…”
Section: Methodsmentioning
confidence: 99%